Elaboração de um manual sobre produção de alimentos e sustentabilidade - PENSADOR, Leticia Estefany Santana (2023)
The sustainability theme is defined as the balance that seeks to satisfy the needs of the current generation, without compromising the capacity of future generations. In this, as food and nutrition units, it establishes itself directly related to the irrational use of natural resources, as well as the increasing generation of solid and nonphysical waste, which improperly disposed of, cause great irreversible damage to the environment. Therefore, this study aims to develop a manual on food production and sustainability in the area of collective food. This is a qualitative descriptive study in which, through bibliographic review, sustainable strategies were listed to compose the manual. In this perspective, this work presents eight structures topics: i) purchase of foodstuffs, ii) rational use of water/energy, iii) preparation technical data, iv) clean leftovers, restintake, v) oil utilization, vi) the water footprint of food, vii) full use of food, viii) educational actions. For the layout of the material, the image bank of the Canva platform was accessed. The result of the manual was personalized with colors and images that were associated with sustainability to draw the attention of the reader and facilitate their awareness. Also, this work presents in its textual composition, a direct and objective language. Finally, it is hoped that the theme of sustainability will be increasingly discussed in the sectors of food production since there is a lack of accessible materials with sustainable practices.